Microwave-assisted evolution of WO3 and WS2/WO3 hierarchical nanotrees. Issue 19 (5th May 2020) - Lee, Noho; Kwak, Junghyeok; Kwak, Ji Hye; Jung, Sang-Mun; Kim, Jaerim; Giri, Anupam; Thiyagarajan, Kaliannan; Kim, Yong-Tae; Jung, Sunshin; Kim, Jong Kyu; Jeong, Unyong
Abstract : Although branched WO3 nanostructures have been investigated for electrochromic devices and catalytic electrodes, a detailed study on their structural evolution mechanism has rarely been carried out. Abstract : Although branched WO3 nanostructures have been investigated for electrochromic devices and catalytic electrodes, a detailed study on their structural evolution mechanism has rarely been carried out. In this work, we have demonstrated the microwave-assisted synthesis of branched WO3 nanotrees consisting of [001]-oriented WO3 needle-like structures growing radially from the surface of WO3 nanohelixes. The mechanism for the evolution of WO3 nanotrees with the preferred orientation was systematically investigated in terms of the reaction temperature and the distribution of the electric field applied by microwave irradiation. In addition, it was shown that the WO3 nanotrees can be easily converted into WS2 /WO3 hierarchical nanotrees by a simple sulfurization process, and used as an efficient catalytic electrode for the hydrogen evolution reaction.